The Validity and Challenges of the Traditional Chieftaincy in Modern Decentralization or Decentralized Governance for Development (DGD) In Lesotho - M., Moses M. (Journal of Education and Vocational Research, 2015)
This is a public management policy system or development administration exploring paper on the country of Lesotho. It is a desk study reviewing the validity of an argument justifying the role of the traditional rule or chieftaincy in the modern ‘decentralized governance for development’ (DGD) or decentralization in Lesotho. The paper discusses chieftaincy and colonialism in Lesotho, institutional roles of chieftaincy, the role of chieftaincy in the era of modern democracy/DGD, the relations between the democratic local authorities and chieftaincy in Lesotho and the role of chieftaincy and its constraints in the decentralized system of Lesotho. The paper directly contributes knowledge in public management sciences and administrative policy systems.